Non-fermentative gram negative bacilli infection and their antimicrobial susceptibility pattern among hospitalized patients in a tertiary care hospital Kathmandu. - Yadav,Santosh Kumar (2018)
ABSTRACT: Background :Non-fermentative gram negative bacilli (NFGNB), frequently considered as commensals or contaminants in past, have now emerged as important nosocomial pathogen causing wide variety of infections in hospitalized patients. The rise in incidence of these infections and resistance to a wide range of commonly used antibiotics necessitates their identification and determination of antibiogram pattern. Objective: The purpose of this study was to isolate and identify non-fermentative gram negative bacilli and determine their antibiotic susceptibility patterns, multidrug resistance (MDR), extended spectrum beta-lactamase (ESBL) production, AmpC production and carbapenemase production. Methods :A cross-sectional descriptive study was conducted at the Department of Clinical Microbiology, Tribhuvan University Teaching Hospital, Kathmandu from February 2017 to January 2018. Ethical approval was taken from the Institutional Review Board of Institute of Medicine, Tribhuvan University and Nepal Health Research Council. The non-fermentative gram negative bacilli isolated from different clinical specimens were identified by standard microbiological testing. Antibiotic susceptibility testing was performed by Kirby Bauer disc diffusion method as per the CLSI guidelines. Multidrug resistance was determined. ESBL production was detected by combination disc method and double-disc synergy test, AmpC production by AmpC disc method and Carbapenemase production was detected by Modified Hodge test. MBL and KPC was detected and differentiated by combination meropenem disc method. Results :A total of 402 non-fermentative gram negative bacilli were isolated from different clinical specimens with isolation rate of 27.1 %. Most of the non-fermenters were isolated from respiratory tract (43.0%) followed by pus and swabs (24.6%), urine (12.2%), blood (6.5%) and CSF (4.5%). The most common non-fermenters were Acinetobacter baumannii (n=177, 44.0%) and Pseudomonas aeruginosa (n=161, 40.0%) and others were Burkholderia cepacia complex (Bcc) (n=33, 8.2%), A. calcoaceticus (n=11, 2.7%), A. lwoffii (n=10, 2.5%), A. haemolyticus (n=3, 0.7%), Stenotrophomonas maltophilia (n=4, 1.0%), P. stutzeri (n=2, 0.5%) and Sphingobacterium multivorum (n=1, 0.2%). The majority of NFGNB were resistant to most of the first line antibiotics tested. The most effective antibiotics were Colistin sulfate and Polymyxin B for Acinetobacter species and Pseudomonas species and Cotrimoxazole for Bcc and Stenotrophomonas maltophilia. Out of 177 A. baumannii isolates, 161(91.0%) were multidrug resistant, 109(61.6%) were MBL producers, 63(35.6%) were AmpC producers, 35(19.8%) ESBL producers and 15(8.5%) were KPC producers. Among P. aeruginosa (n=161), 118(73.3%) were MDR, 75(46.6%) were MBL producers, 48(29.8%) were ESBL producers and 17(10.6%) were KPC producers. Out of 33 isolates of Bcc, 26 (78.8%) were MDR, 14 (42.2%) were ESBL producer and 8 (24.2%) were MBL producer. Conclusion : From the present study it is clear that, non-fermenters can cause vast variety of infections in hospitalized patients. Most of the non-fermenters causing infections in the hospitalized patients were Acinetobacter baumannii and Pseudomonas aeruginosa. Higher rates of MDR strains were common among these bacteria, which is particularly worrisome. ESBL and MBL producing isolates were common among these bacteria and their rate has highly increased than that of previous studies and these bacteria lead to high morbidity and mortality as we are left with the only option of treating them by potentially toxic antibiotics like Colistin sulfate and Polymyxin B. Care in detection, evaluation of effective antibiotic options, judicious use of antibiotics and rigorous infection control measures will help to fight against these multidrug resistant non-fermenters in the effective management of patients. Key words : Acinetobacter baumannii, MBL, multidrug resistance, non-fermentative gram negative bacilli, Pseudomonas aeruginosa